Nanomedicine associated with photodynamic therapy for glioblastoma treatment - de Paula, Leonardo B.; Primo, Fernando L. [UNESP]; Tedesco, Antonio C. (Springer Nature, 2017)
Glioblastoma, also known as glioblastoma multiforme (GBM), is the most recurrent and malignant astrocytic glioma found in adults. Biologically, GBMs are highly aggressive tumors that often show diffuse infiltration of the brain parenchyma, making complete surgical resection difficult. GBM is not curable with surgery alone because tumor cells typically invade the surrounding brain, rendering complete resection unsafe. Consequently, present-day therapy for malignant glioma remains a great challenge. The location of the invasive tumor cells presents several barriers to therapeutic delivery. The blood–brain barrier regulates the trafficking of molecules to and from the brain. While high-grade brain tumors contain some “leakiness” in their neovasculature, the mechanisms of GBM onset and progression remain largely unknown. Recent advances in the understanding of the signaling pathways that underlie GBM pathogenesis have led to the development of new therapeutic approaches targeting multiple oncogenic signaling aberrations associated with the GBM. Among these, drug delivery nanosystems have been produced to target therapeutic agents and improve their biodistribution and therapeutic index in the tumor. These systems mainly include polymer or lipid-based carriers such as liposomes, metal nanoparticles, polymeric nanospheres and nanocapsules, micelles, dendrimers, nanocrystals, and nanogold. Photodynamic therapy (PDT) is a promising treatment for a variety of oncological diseases. PDT is an efficient, simple, and versatile method that is based on a combination of a photosensitive drug and light (generally laser-diode or laser); these factors are separately relatively harmless but when used together in the presence of oxygen molecules, free radicals are produced that initiate a sequence of biological events, including phototoxicity, vascular damage, and immune responses. Photodynamic pathways activate a cascade of activities, including apoptotic and necrotic cell death in both the tumor and the neovasculature, leading to a permanent lesion and destruction of GBM cells that remain in the healthy tissue. Glioblastoma tumors differ at the molecular level. For example, gene amplification epidermal growth factor receptor and its receptor are more highly expressed in primary GBM than in secondary GBM. Despite these distinguishing features, both types of tumors (primary and secondary) arise as a result dysregulation of numerous intracellular signaling pathways and have standard features, such as increased cell proliferation, survival and resistance to apoptosis, and loss of adhesion and migration, and may show a high degree of invasiveness. PDT may promote significant tumor regression and extend the lifetime of patients who experience glioma progression.
Keywords: Drug delivery nanosystems; Glioblastoma multiforme; Signaling pathways